XTEA CRYPTOGRAPHY IMPLEMENTATION IN ANDROID CHATTING APP - Irfan Syamsuddin; Siska Ihdianty; Eddy Tungadi; Kasim Kasim; Irawan Irawan (Journal of Information Technology and Its Utilization, 2020)
Information security plays a significant role in information society. Cryptography is a key proof of concept to increasing the security of information assets and has been deployed in various algorithms. Among cryptography algorithms is Extended Tiny Encryption Algorithm. This study aims to describe a recent Android Apps to realize XTEA Cryptography in mobile form. In addition, a thorough example is presented to enable readers gain understanding on how it works within our Android Apps.